Influences of impulse generators on the impulse characteristics of grounding systems - Muhammad, Usman; Aman, Fazlul; Mohamad Nor, Normiza; Nadia Ahmad, Nurul; Osman, Miszaina (Bulletin of Electrical Engineering and Informatics, 2025)
It is important to ensure the effectiveness of the experimental test set up and to accurately characterize grounding systems under high impulse conditions, the study on the effect of impulse generator is therefore needed. As with other experimental work, the test results may be influenced not only by the characteristics of the test load under study, but also the test arrangement, rating of the impulse generator and transducers. In this work, sources of this overshoot/spike observed in voltage and current traces of 1-rod, 3-rod, and 4-rod electrodes subjected to two impulse current generators of different rating: generating at maximum voltage and current of 100 kV, 1.5 kA, and 300 kV, 10 kA with the same response time of 1.2/50 μs are identified with the aid of simulation work.